2005
DOI: 10.5511/plantbiotechnology.22.71
|View full text |Cite
|
Sign up to set email alerts
|

Physiological functions of plant DNA methyltransferases

Abstract: Among factors that regulate gene expression in eukaryotes, DNA methylation, chromatin remodeling and modification of N-termini of core histones are considered to play key roles. All of these are epigenetic and recent studies have provided much information on the molecular basis of such modification and interrelationships between DNA and chromatin modification in regulation of normal development. Epigenetic modification in plants is particularly responsive to environmental stimuli. In this article, I briefly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 103 publications
1
15
1
Order By: Relevance
“…Methylation of plant DNA occurs in all sequence contexts (i.e., CG, CHG and CHH), whereas methylation in mammals is largely restricted to CG sites and there is no evidence for extensive methylation of asymmetric CHH sites. 42 Although Jones et al 18 and Aufsatz et al 43 suggested that methylation in the asymmetrical CHH sites cannot be maintained efficiently in the absence of RNA signals, we detected the maintenance of asymmetrical CHH methylation in the progeny plants that have no RNA trigger, even though the extent of methylation was reduced through the meiosis (Fig. 7).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 69%
“…Methylation of plant DNA occurs in all sequence contexts (i.e., CG, CHG and CHH), whereas methylation in mammals is largely restricted to CG sites and there is no evidence for extensive methylation of asymmetric CHH sites. 42 Although Jones et al 18 and Aufsatz et al 43 suggested that methylation in the asymmetrical CHH sites cannot be maintained efficiently in the absence of RNA signals, we detected the maintenance of asymmetrical CHH methylation in the progeny plants that have no RNA trigger, even though the extent of methylation was reduced through the meiosis (Fig. 7).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 69%
“…Appropriate DNA methylation patterns which are established and maintained by DNA methyltransferases (DNMTs) are essential for correct development and tissue differentiation (Cao et al 2000;Finnegan and Kovac 2000;Huang et al 2010;Wada 2005). To study the involvement of DNA methylation in this process, we first characterized the structure of the four types of DNA methyltransferases (QsDNMTs) and one associated protein, DMAP1, in Q. suber.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the epigenetic regulation of plant developmental steps is widely recognized (Finnegan and Kovac 2000;Huang et al 2010;Wada 2005). Epigenetic phenomena are associated with several chromatin modifications being DNA methylation, a heritable DNA modification, the best studied (Martienssen and Colot 2001).…”
Section: Communicated By D Nealementioning
confidence: 99%
“…On the other hand, the domains rearranged methyltransferase (DRM) class and the chromomethylase (CMT) class of DNA methyltransferases in Arabidopsis are involved in methylation of non-CpG sequences (Tariq M and Paszkowski 2004). DRM class methyltransferases have homology to mammalian Dnmt3 de novo methyltransferase, whereas CMT class methyltransferases are unique to plants, and maintain non-CpG (primarily CpHpG) methylation (Vaillant and Paszkowski 2007;Wada 2005). The genome-wide bisulfite sequencing study revealed that CpHpG methylation on one strand was highly correlated with CpHpG methylation on the opposing strand (Cokus et al 2008); however, the maintenance DNA methylation machinery for hemimethylated CpHpG sites is still unclear.…”
mentioning
confidence: 99%